Design of a Novel Creel Conditioning System for Circular Knitting Machines - Filiz Yıldırımkaraman; Arzu Marmarali; Nida Oğlakcıoğlu (Tekstilec, 2024)
Maintaining a certain humidity level of humidity in yarn packages and removing fibre fly from the environment is very important for production efficiency and product quality in textile mills. Humidity has a significant effect on the quality and efficiency of fabrics, especially those made from hydrophilic fibres. The high temperature and low humidity level in the factory environment results in lower yarn strength and higher yarn breakage. The solution is to provide optimum temperature and humidity levels through a central air conditioning system. However, conditioning the entire factory environment is an expensive approach and does not facilitate satisfactory production efficiency. In this study, a new creel system for circular knitting machines was designed to provide excellent yarn package conditioning. More efficient production and economical conditioning were achieved with this new creel system.